2019
DOI: 10.1039/c9ra07399j
|View full text |Cite
|
Sign up to set email alerts
|

New dimensions in calix[4]pyrrole: the land of opportunity in supramolecular chemistry

Abstract: The quest for receptors endowed with the selective complexation and detection of negatively charged species continues to receive substantial consideration within the scientific community worldwide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 188 publications
(250 reference statements)
1
41
0
Order By: Relevance
“…Basically, our interest to generate pyrrole-based C 3 -symmetric truxene derivatives was because of a range of applications of the pyrrole moiety in diverse fields, for instance, a wide variety of medicinally active as well as smart functional materials possessing the pyrrole as a fundamental subunit [28][29][30]. Additionally, 3,4disubstituted pyrrole derivatives are versatile building blocks for the production of diverse bioactive molecules like co-enzyme, alkaloids, porphyrins and other related macrocycles [31,32]. Moreover, polypyrrolic systems are of extensive interest in numerous areas namely optics, medicine, and supramolecular chemistry in addition to the materials sciences and technology.…”
Section: Resultsmentioning
confidence: 99%
“…Basically, our interest to generate pyrrole-based C 3 -symmetric truxene derivatives was because of a range of applications of the pyrrole moiety in diverse fields, for instance, a wide variety of medicinally active as well as smart functional materials possessing the pyrrole as a fundamental subunit [28][29][30]. Additionally, 3,4disubstituted pyrrole derivatives are versatile building blocks for the production of diverse bioactive molecules like co-enzyme, alkaloids, porphyrins and other related macrocycles [31,32]. Moreover, polypyrrolic systems are of extensive interest in numerous areas namely optics, medicine, and supramolecular chemistry in addition to the materials sciences and technology.…”
Section: Resultsmentioning
confidence: 99%
“…[4,5] Infact, the interaction of amides with biological and supramolecular receptors through intermolecular interactions is considered as the key aspect in the domain of drug discovery as well as supramolecular chemistry. [6][7][8][9][10][11] Moreover, the amide bonds possess an inherent tendency to participate in diverse vital transformations, hence are synthetically versatile. [12,13] In stark contrast, bisamides possessing amide groups constitute an interesting and important class of organic compounds and are certainly the vital scaffolds for peptidomimetics [14][15][16][17] besides their applicability in a vast variety of bioactive molecules like antidepressants as well as anticancer drugs, Scholarisine G (1) and Leconoxine (2), [18] antimicrobial and antioxidant JBIR-94 (3), [17] cannabinoid type 2 (CB2) receptor inverse agonist and XIE95PY1 osteoclast inhibitor (4-6) (Figure 1) etc.…”
Section: Introductionmentioning
confidence: 99%
“…[5] Scientists around the globe are constructing diverse artificial anion receptors, which mimic the function of biosystems and involve anion-π interactions besides other non-covalent interactions in the recognition phenomenon of anions. [6] From the recent theoretical, computational, and experimental investigation, it has been observed that anion-π interactions have shown a promising role in supramolecular catalysis and has given rise to a new concept of anion-π catalysis. The emerging field of anion-π catalysis has not yet much explored in chemistry and until now only few reports are available in literature.…”
Section: Introductionmentioning
confidence: 99%